A multi-functional macrophage and tumor targeting gene delivery system for the regulation of macrophage polarity and reversal of cancer immunoresistance. Issue 33 (9th August 2018) - He, Xiao-Yan; Liu, Bo-Ya; Xu, Chang; Zhuo, Ren-Xi; Cheng, Si-Xue
Abstract : A macrophage and tumor targeting delivery system of pDNA IL-12 can effectively regulate macrophage polarity and reverse cancer immunoresistance. Abstract : To achieve effective tumor eradication using anti-tumor immunotherapies, a fusion peptide functionalized gene delivery system for macrophage and tumor targeting delivery of the plasmid DNA encoding the IL-12 gene (pDNA IL-12) was prepared for macrophage re-polarization as well as reversal of cancer immunosuppression. A fusion peptide containing the tuftsin sequence that can interact with Fc receptors and neuropilin-1, and hyaluronic acid (HA) that can interact with CD44 were introduced into the delivery system by self-assembly to form peptide/hyaluronic acid/protamine/CaCO3 /DNA nanoparticles (PHNP) with both macrophage targeting and tumor targeting capabilities. PHNP provides an efficient immunoregulation on J774A.1 cells to shift the anti-inflammatory M2 phenotype to the anti-tumor M1 phenotype with enhanced secretion of pro-inflammatory cytokines and increased expression of M1 markers. Owing to the improved delivery efficiency caused by the fusion peptide and HA, the transfection mediated by multi-functional PHNP can up-regulate IL-12 as well as down-regulate IL-10 and IL-4 more effectively as compared with the nanoparticles without HA and/or peptide decoration. More importantly, the gene delivery system can also deliver pDNA IL-12 to targeted cancerous HeLa cells to realize the secretion of IL-12. PHNP not only enables tumorous cells to produce pDNA IL-12, but also down-regulates CD47 and up-regulate CD80 and HLA-1 in the malignant cells, indicating that the gene delivery system can effectively reverse tumor induced immunosuppression.